The Cambridge Dictionary of Statistics - Everitt, Brian (Gale virtual reference library, 2002)
If you use statistics and need a useful, up-to-date reliable sourcebook that provides simple definitions and explanations of statistical and statistics-related concepts, then look no further than this dictionary. Some 3500 terms are defined, a considerable increase over the first edition. Short biographies of over 100 important statisticians are included.